Saikosaponin D Inhibits Peritoneal Fibrosis in Rats With Renal Failure by Regulation of TGFβ1/ BMP7 / Gremlin1/ Smad Pathway - Ruiqi, Liu; Ming, Pei; Qihang, Su; Yangyang, Lei; Junli, Chen; Wei, Lin; Chao, Gao; Xinyue, Liu; Kang, Yang; Hongtao, Yang (Frontiers in Pharmacology, 2021)
Peritoneal dialysis (PD) is an effective way to improve the quality of patients’ life and extend their survival time. However, peritoneal fibrosis as a main cause for PD withdrawal. Therefore, it is significantly urgent to understand how to inhibit and slow down the progression of peritoneal fibrosis. This aim of this study is to evaluate the degree of TGFβ1/BMP7/Gremlin1 pathway cross-talk contribute to affect the regulatory effect of SSD(Saikosaponin d）on peritoneal fibrosis by using rats as model. We performed studies in rat with chronic kidney disease after 5/6 nephrectomy and peritoneal fibrosis . Rats were categorized into four groups: (i) Control group: 15 ml saline was injected intraperitoneally every day. Rats received normal saline (10ml\kg) by gavage once daily. (ii) Model group: 15ml 4.25% dialysate was injected intraperitoneally every day. Rats received normal saline (10ml\kg) by gavage once daily. (iii) SSD group: 15ml 4.25% dialysate was injected intraperitoneally every day. Rats received SSD (5mg\kg) (with 0.5%NaCMC) by gavage once daily. (iv) Positive drug group (M+A group): 15ml 4.25% dialysate was injected intraperitoneally every day. Rats received Benazepril Hydrochloride (5mg\kg) by gavage once daily. Rates were interfered for four weeks. We found that the peritoneal fibrosis was successfully formed according to pathological findings. WB, ELISA and PCR detection results showed that TGFβ1 and Gremlin1 levels in group M were significantly higher than those in group C.Compared with group C, BMP7 expression was significantly decreased.TGFβ1 and Gremlin1 levels of rats after SSD intervention were significantly lower than those in M group.The expression of BMP7 in SSD group was significantly increased.In addition, the SMAD1/5/8 level of PCR and the p-SMAD1/5/8 expression of WB in SSD group were also significantly higher than those in M group.Levels of vimentin and α-SMA, which are closely related to fibrosis, were significantly reduced.Our research has demonstrated that the TGFβ1 / BMP7 /Gremlin1/Smad pathway may be a potential therapeutic target for peritoneal fibrosis and has also proved that SSD is a monomer that can reverse peritoneal fibrosis by regulating this pathway.